2009
DOI: 10.1074/jbc.m805429200
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Induces Interleukin-8 (IL-8) Gene Expression in Human Conjunctiva through the Recruitment of Both RelA and CCAAT/Enhancer-binding Protein β to the IL-8 Promoter

Abstract: The purpose of this study was to identify the Pseudomonas aeruginosa-activated signaling pathway leading to interleukin (IL)-8 gene expression and protein synthesis by human conjunctival epithelium. IL-8 protein and mRNA were determined by enzyme-linked immunosorbent assay and reverse transcription-PCR, respectively. Activation of MAPKs and NF-B was analyzed by Western blotting using phosphospecific antibodies. We used transfection with wild-type or mutated IL-8 promoters and cotransfection with transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 50 publications
(24 reference statements)
1
19
0
Order By: Relevance
“…Zhang et al have demonstrated a functional relationship between these two transcription factors in chondrocytes in response to IL-1b, 44 and coregulation by NF-kB and C/EBPb of genes in a variety of other cell types has been demonstrated. [45][46][47] These data are consistent with the ability of NF-kB and C/EBPb to block the expression of Sox9, 48 a transcription factor that is essential for chondrogenesis, and for repression of type II collagen expression. 49 Moreover, evidence suggests that C/ EBPb enhances NF-kB-associated signaling by negatively regulating the level of the NF-kB inhibitor IkB-a.…”
Section: Control) (D)supporting
confidence: 71%
“…Zhang et al have demonstrated a functional relationship between these two transcription factors in chondrocytes in response to IL-1b, 44 and coregulation by NF-kB and C/EBPb of genes in a variety of other cell types has been demonstrated. [45][46][47] These data are consistent with the ability of NF-kB and C/EBPb to block the expression of Sox9, 48 a transcription factor that is essential for chondrogenesis, and for repression of type II collagen expression. 49 Moreover, evidence suggests that C/ EBPb enhances NF-kB-associated signaling by negatively regulating the level of the NF-kB inhibitor IkB-a.…”
Section: Control) (D)supporting
confidence: 71%
“…Upon stimulation, C/EBP-b can regulate the expression of target genes by increasing their protein levels (44,45). In addition, phosphorylation of C/EBP-b protein on Thr 235 increases the binding of coactivator p300 and CBP to C/EBP-b, which can regulate its transcriptional activity (46,47). We found that HSV-2 infection did not increase the protein level of C/EBP-b, but rather It has been previously demonstrated that MAPKs phosphorylate C/EBP-b protein on Thr 235 and regulate its transcriptional activity (48).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that NF-kB and AP-1 are widely established as TFs implicated in the expression of IL-8 gene in different cell models (27,34), other TFs have been recently reported as possible regulators of IL-8 gene transcription, such as the TF CHOP in Tlymphocytes and in human bronchial IB3-1 cells (30,47), the TF CREB in U937 monocytic cells and in A549 cells (28,48), and the TF NF-IL6 in human conjunctival and bronchial cells induced by P. aeruginosa (48). To build a comprehensive picture of the different TFs intervening in human bronchial epithelial cells challenged with P. aeruginosa, we first made an in silico analysis of the proximal region of the IL-8 gene promoter (from start site up to 2180 bp) with the TF search software TESS (http://www.cbil.…”
Section: Development Of Tf Decoy Odns To Interfere With Il-8 Gene Tramentioning
confidence: 99%